2016
DOI: 10.22159/ijpps.2016v8i10.5788
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Medicinal Plant Species of Djiboutian Pharmacopeia for Testing Pharmacological Activities on Common Microbial Diseases

Abstract: Objective: The aim of the study was to conduct an ethnobotanical study focused on the medicinal plants used in Randa (Djibouti) for testing pharmacological activities on common microbial diseases.Methods: Plant Ratio (PR), Index of Performance (IP) and the high Informant Consensus Factors (ICF) were calculated to select candidate medicinal species with a pharmacological potential. Results:From this previous work, it was found that the high Informant Consensus Factors, ICF (0.82) for the category of microbial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Several studies conducted in recent decades revealed that extracts from the bark of A. seyal have antibacterial action [25,38,39], antimalarial effect [40], antimycobacterial effect, cyclooxygenase inhibition effect [41], molluscicidal activity [42], and anticancer activities [43,44]. Acacia gum has been established to possess several therapeutic actions, such as hypoglycemic, antidiabetic, antioxidant, immunomodulatory, and cytoprotective antiulcer, and has prebiotic properties [18,25].…”
Section: Medicinal Usesmentioning
confidence: 99%
“…Several studies conducted in recent decades revealed that extracts from the bark of A. seyal have antibacterial action [25,38,39], antimalarial effect [40], antimycobacterial effect, cyclooxygenase inhibition effect [41], molluscicidal activity [42], and anticancer activities [43,44]. Acacia gum has been established to possess several therapeutic actions, such as hypoglycemic, antidiabetic, antioxidant, immunomodulatory, and cytoprotective antiulcer, and has prebiotic properties [18,25].…”
Section: Medicinal Usesmentioning
confidence: 99%
“…Many clinically useful prescription drugs have originated from traditional medicinal plants. Since there are many traditional medicinal plants widely used by society, it is worth subjecting these plants to investigate for the discovery of drugs with anticipation of obtaining new bioactive substances [1].…”
Section: Introductionmentioning
confidence: 99%
“…The method allows the growth of plant materials that otherwise would be difficult to grow in nature because of geographic, climatic, or seasonal restrictions. From the plant materials, the production of secondary metabolites can also be manipulated in vitro, which can lead to overproduction of compounds of interest, or the production of chemicals not originally found in native plants [1].…”
Section: Introductionmentioning
confidence: 99%